Metal-as-insulation variant of no-insulation HTS winding technique: pancake tests under high background magnetic field and high current at 4.2 K. (4th April 2018) - Lécrevisse, T; Badel, A; Benkel, T; Chaud, X; Fazilleau, P; Tixador, P
Abstract: In the framework of a project aiming at fabricating a 10 T high temperature superconducting (HTS) insert to operate in a 20 T background field, we are investigating the behavior of pancakes consisting of a REBCO HTS tape co-wound with a stainless steel tape (metal-as-insulation (MI) coil). The MI winding is inducing a significant turn-to-turn electrical resistance which helps to reduce the charging time delay. Despite this resistance, the self-protection feature of no-insulation coils is still enabled, thanks to the voltage limit of the power supply. We have built a single pancake coil representative of the pancake that will be used in the insert and performed tests under very high background magnetic field. Our coil experienced over 100 heater induced quenches without a measureable increase of its internal resistance. We have gathered stability and quench behavior data for magnetic fields and engineering current densities ( je ) in the range of 0–17 T and 0–635 A mm −2 respectively. We also present our very first experiments on the insert/outsert interaction in the case of a resistive magnet fault. We show that if self-protection of the MI winding is really effective in the case of a MI coil quench, a major issue comes from the outsert fault which induces a huge current inside the MI coil.